PELAKSANAAN INOVASI PELAYANAN PROGRAM 3 IN 1 DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK (STUDI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BATU) - Viktoria Ndia; Cahyo Sasmito (Universitas Tribhuwana Tunggadewi, 2019)
Abstract:The condition of the regional government in carrying out public services has not been running well, and even seems to be far from the expectations of the people and the normative demands for regional autonomy (Mulyadi, Dedy. Et al. 2018: 58). From the data belonging to the Batu City Population and Civil Registration Service, only 40 percent of the residents had birth certificates. This study aims to determine the Implementation of the 3 In 1 Service Innovation Program in Improving the Quality of Public Services, Supporting Factors and Obstacle Factors. Qualitative research methods. Primary and secondary data sources. Data collection techniques: observation, interviews, and documentation. Informant Determination Technique: purposive sampling. The researcher's own instruments, interview guidelines, and field notes. Data Analysis: Data Reduction, Data Presentation, Draw Conclusions. Data robustness test uses technique triangulation. The results of the study show that the Implementation of Service Innovation in the 3 In 1 Program at the Dispendukcapil in Batu City has been able to run effectively and efficiently in supporting the improvement of the quality of public services. The inhibiting factor is that there are still many people who cannot access online and the biodata differences on the Family Card with the Marriage Certificate. While the supporting factors are adequate facilities and infrastructure and the competence of service providers is good, as well as cooperation between Dispendukcapil and Hospitals / Puskesmas in Batu City. Keywords: Quality of Public Service, Public Service Innovation, Service Program 3 In 1Abstrak: Kondisi pemerintah daerah menyelenggarakan pelayanan publik belum berjalan secara baik, bahkan terkesan masih jauh dari harapan masyarakat dan tuntutan normatif diberlakukannya otonomi daerah (Mulyadi, Dedy., dkk. 2018: 58). Dari data milik Dinas Kependudukan dan Pencatatan Sipil Kota Batu, baru mencatat 40 persen warga yang memiliki akta kelahiran. Penelitian ini bertujuan untuk mengetahui Pelaksanaan Inovasi Pelayanan Program 3 In 1 Dalam Meningkatkan Kualitas Pelayanan Publik, Faktor Pendukung dan Faktor Penghambatnya. Metode penelitian kualitatif. Sumber Data primer dan sekunder. Teknik pengumpulan data: observasi, wawancara, dan dokumentasi. Teknik Penentuan Informan: purposive sampling. Instrumen penelitian peneliti sendiri, pedoman wawancara, dan catatan lapangan. Analisis Data: Reduksi Data, Penyajian Data, Penarikan Kesimpulan. Uji kebsahan data menggunakan triangulasi teknik. Hasil penelitian menunjukkan Pelaksanaan Inovasi Pelayanan Program 3 In 1 Pada Dispendukcapil Kota Batu sudah dapat berjalan dengan efektif dan efisien dalam menunjang peningkatan kualitas pelayanan publik. Faktor Penghambat adalah masih banyak masyarakat yang belum bisa mengakses secara online dan perbedaan biodata pada Kartu Keluarga dengan Akta Nikah. Sedangakan faktor pendukungnya adalah sarana dan prasarana yang cukup memadai dan kompetensi petugas pemberi pelayanan sudah baik, serta kerjasama antara Dispendukcapil dengan Rumah Sakit/Puskesmas di Kota Batu. Kata Kunci: Kualitas Pelayanan Publik, Inovasi Pelayanan Publik, Pelayanan Program 3 In 1